Twelve years experience with radical hysterectomy and pelvic lymphadenectomy in early stage cervical cancer - P. Suprasert (2018)
The objective of this study was to evaluate the outcome, prognostic factors and complications of early stage cervical cancer patients treated with radical hysterectomy and pelvic lymphadenectomy (RHPL). The medical records of cervical cancer patients undergoing RHPL at Chiang Mai University Hospital over 12 years, between January 1995 and December 2006 were reviewed. There were 1,253 patients in the study period. The mean age was 44 years of age. Of these, 26.9 had prior diagnostic conisation. The maximum tumour size was 8cm. The most common histology was squamous cell carcinoma (67) followed by adenocarcinoma (23). The distribution of FIGO staging was: stage IA 8.7; stage IB 15.8; stage IB1 61; stage IB2 6.2; and stage IIA 8.5. Pelvic nodes, parametrial and vaginal margin involvement were detected in 15.9, 10.7 and 3.8 of the patients, respectively. A total of 66.5 of patients underwent RHPL without adjuvant treatment; 12.1 received neoadjuvant chemotherapy. The estimated 10-year recurrence-free survival rate was 90. Stage IB2/IIA, non-squamous cell carcinoma, nodal involvement and positive vaginal margins were independent, significant, poor prognostic factors. The most common long-term complication was lymphoedema. It was concluded that early stage cervical cancer patients treated with RHPL have long-term favourable outcome with minimal morbidity. Stage IB2 and IIA, non-squamous cell carcinoma, nodal and vaginal involvement were independent adverse prognostic factors. © 2010 Informa Healthcare USA, Inc.